Morphology of the early larval stages of Lysmata ankeri Rhyne & Lin, 2006 and Lysmata bahia Rhyne & Lin, 2006 (Caridea: Lysmatidae) and a review of the larval morphology of the early Lysmata stages - Almeida, Andréa Santos E; Alves, Douglas Fernandes Rodrigues; Barros-Alves, Samara De Paiva; Pescinelli, Régis Augusto; Costa, Rogério Caetano Da (Zootaxa, 2023)
The early larval stages of the shrimps Lysmata ankeri and L. bahia were described, illustrated, and compared among other Lysmata species, providing important information on post-embryonic development and insights into its evolutionary history. Ovigerous specimens of L. ankeri and L. bahia were sampled from southeastern and northeastern Brazilian coast, respectively. For L. ankeri and L. bahia, five and three larval stages were obtained, respectively. Unique features were observed for L. ankeri and L. bahia larvae, and some characteristics may differ only for L. ankeri and L. bahia, which were not observed in the other species analyzed, such as: presence of a pair of simple setae on the third pleonal somite in zoea I and number of setae on the uropod exopod greater than 11. Moreover, several other features are similar between species from the diferent clades of the Lysmata-Exhippolysmata complex, making it possible to identify the early stages of Lysmata larvae. However, future studies will be essential to confirm or not the existence of some phylogenetic patterns and their relevance and other larval characters for better understanding the evolutionary history of this group.